Analisis Jenis Pohon dan Tingkat Kesehatan Pohon Pelindung Pada Jalur Hijau di Kota Kotamobagu - Rempas, Robby D.J; Amon, Hendra; Masero, Widia Lestari (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
City development plays a very important role in the city environment itself because of the large influence it can have, one of which is the loss of the natural environment resulting in its function in the ecosystem also continuing to be lost. The purpose of this research is to analyze the types of protective trees and their health in the green belt in Kotamobagu City. The method used in this research is the survey method. There are 2 general data collection stages in this research, namely primary data and secondary data and using a percentage formula as a benchmark to see the health level of protective trees in Kotamobagu City. This requires intensive activities to minimize damage to the protective trees. As a result of the research, it was found that intensive activities were needed, including the maintenance and management of protective trees on the green lane of the road. Maintenance of protective trees includes pruning, felling (for trees that are old and have the potential to fall), wound care, staking, controlling pests, diseases and invasive plants and replanting. The management includes making boards prohibiting the sticking of advertising banners on protective trees, prohibiting burning and dumping rubbish near trees, recording planting times, using tree seeds that are suitable for urban areas, conducting outreach to the community and monitoring regularly to prevent accidents or material loss due to fallen trees.